The Interface Between Veterinary and Behavioral Management of Chimpanzees (Pan troglodytes) in a United States Sanctuary Demonstrated by Two Clinical Cases - Raven Jackson; Rebekah Lewis; Amy Fultz (Veterinary Sciences)
Chimp Haven is a private, nonprofit organization that serves as the largest chimpanzee sanctuary in the world. The National Institutes of Health supports the federal sanctuary system, which is operated by Chimp Haven, to provide lifetime care for chimpanzees who have retired from biomedical research. Chimp Haven is home to over 300 chimpanzees, with a wide variety of individual health needs including infectious diseases. The chimpanzees live in large, mixed-sex social groups within corrals, multi-dimensional enclosures, and naturally forested habitats, which presents challenges for monitoring and balancing individual versus group needs. Primate veterinarians and animal behavior directors have an obligation to collaborate for the best possible health and welfare outcomes for the species in their care. This manuscript details how veterinarians and behavioral staff at Chimp Haven interface to enhance clinical management and improve chimpanzee welfare using two clinical cases to illustrate this relationship. This is accomplished through the development of individual care plans that include the utilization of welfare assessment metrics and positive reinforcement training programs collaboratively developed between the veterinarians and behaviorists to facilitate voluntary medical procedures without the need for social isolation. Specifically, welfare metrics such as monitoring chimpanzee wounding levels and severity, as well as targeted assessments, involve the input of both the veterinarians and behaviorists. Positive reinforcement training initiatives such as weight loss, heart health, and wound care also require the interface between the two disciplines. The authors aim to demonstrate that working together provides optimal levels of expert care for both the physical and mental health of the chimpanzees in our care.